Porous ceramic loaded SnO2-SnO catalyst, preparation method thereof and method for preparing ethyl methacrylate by using porous ceramic loaded SnO2-SnO catalyst

By using a porous ceramic-loaded SnO2/SnO catalyst to perform a transesterification distillation system, the problems of low raw material conversion and difficult catalyst treatment in the preparation of ethyl methacrylate in the prior art are solved, and high selectivity and efficient continuous production are achieved, and environmentally friendly and waste liquid generation is not generated.

CN119793437APending Publication Date: 2025-04-11WANHUA CHEM GRP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510001238.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art has low raw material conversion rate, difficult catalyst treatment, and large waste liquid production when preparing ethyl methacrylate, making it difficult to achieve high selectivity and efficient continuous production.

Method used

The transesterification reaction between methyl methacrylate and ethanol is carried out through a porous ceramic-supported SnO2/SnO catalyst, thereby achieving high selectivity and high conversion rate production of ethyl methacrylate.

Benefits of technology

It achieves high selectivity (greater than 99%) and high ethanol conversion (greater than 99.8%) of ethyl methacrylate, generates wastewater without catalysts, is green and environmentally friendly, and is suitable for large-scale continuous production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793437A_ABST
    Figure CN119793437A_ABST
Patent Text Reader

Abstract

The invention provides a porous ceramic loaded SnO2 / SnO catalyst, a preparation method thereof and a method for preparing ethyl methacrylate by using the porous ceramic loaded SnO2 / SnO catalyst. The porous ceramic loaded SnO2 / SnO catalyst is a spherical aluminum titanate porous ceramic loaded SnO2 / SnO catalyst. The porous ceramic loaded SnO2 / SnO catalyst is a solid catalyst capable of catalyzing transesterification of methyl methacrylate and ethyl alcohol, when the catalyst is used in preparation of ethyl methacrylate, the conversion rate of ethyl alcohol is high, the selectivity of ethyl methacrylate is high, continuous production operation of ethyl methacrylate can be achieved, and the method is suitable for industrial production. The whole process does not generate catalyst wastewater and waste liquid and is green and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic compound preparation, and specifically relates to a porous ceramic-loaded SnO2 / SnO catalyst, a preparation method and use thereof, and a preparation method for ethyl methacrylate. Background Art

[0002] Ethyl methacrylate has a wide range of uses. It can be used not only to make acrylic copolymers, adhesives and coatings, but also in organic synthesis and the preparation of organic glass, and is also used as a solvent. It can be copolymerized with other monomers to obtain ester copolymers, which are widely used in the coating industry, adhesives, fiber treatment agents and molding materials.

[0003] At present, there are two methods for preparing ethyl methacrylate: direct esterification and transesterification. The direct esterification method mainly uses methacrylic acid and ethanol to react under acidic catalyst conditions to synthesize, while the transesterification method uses methyl methacrylate and ethanol to react under transesterification catalyst conditions to prepare.

[0004] CN201210258455.4 discloses a method for preparing ethyl methacrylate, which adopts a direct esterification process, takes methacrylic acid and anhydrous ethanol as raw materials, and reacts to generate ethyl methacrylate under the action of a catalyst and an inhibitor. During the reaction, ethanol is excessive and acts as a water-carrying agent. The conversion rate of methacrylic acid is low, only 92-93%. The subsequent separation unit needs to consider the separation of methacrylic acid, which increases equipment investment.

[0005] The catalysts used in the ester exchange process to prepare ethyl methacrylate are mostly homogeneous catalysts. After the reaction is completed, the product refining unit needs to consider its removal, generating waste liquid containing the catalyst.

[0006] Due to the problems of low raw material conversion rate, difficult catalyst treatment and large amount of waste liquid generated in the preparation of ethyl methacrylate by traditional direct esterification and ester exchange methods, it is urgent to develop a continuous production process using new reaction types and catalyst types to achieve high selectivity of ethyl methacrylate products, high raw material conversion rate, continuous process, and green environmental protection. Summary of the invention

[0007] The invention provides a porous ceramic-loaded SnO2 / SnO catalyst and a preparation method thereof. The porous ceramic-loaded SnO2 / SnO catalyst is a solid catalyst capable of catalyzing methyl methacrylate and ethanol to carry out an ester exchange reaction. When the catalyst is used in the preparation of ethyl methacrylate, the conversion rate of ethanol is high, the selectivity of ethyl methacrylate is high, and the continuous production operation of ethyl methacrylate can be realized. No catalyst wastewater or waste liquid is generated in the whole process, and the catalyst is green and environmentally friendly.

[0008] Another object of the present invention is to provide the use of the porous ceramic-supported SnO2 / SnO catalyst, in particular, the use of the porous ceramic-supported SnO2 / SnO catalyst in preparing ethyl methacrylate.

[0009] In order to achieve the above invention object, the technical solution adopted by the present invention is as follows:

[0010] A porous ceramic-supported SnO2 / SnO catalyst, wherein the supported catalyst uses aluminum titanate porous ceramic prepared by using zinc carbonate / calcium carbonate as porogens as a carrier, and the supported active component is a SnO2 / SnO mixture, and the tin content in the catalyst is 5-20wt%, for example, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, etc., preferably 10-15wt%, based on the total mass of the catalyst.

[0011] On the other hand, a method for preparing the above-mentioned porous ceramic-supported SnO2 / SnO catalyst comprises the following steps:

[0012] (1) Using aluminum titanate powder as a raw material, a mixture of zinc carbonate and calcium carbonate as a porogen, and magnesium oxide as a stabilizer, and calcining at elevated temperatures to obtain aluminum titanate porous ceramics;

[0013] (2) soaking the aluminum titanate porous ceramic obtained in step (1) in a saturated glycerol solution of tin nitrate and stannous nitrate so that the tin nitrate and stannous nitrate adhere to the inside of the porous ceramic particles to obtain a porous ceramic / tin salt composite material;

[0014] (3) The porous ceramic / tin salt composite material obtained in step (2) is calcined and granulated to obtain a spherical aluminum titanate porous ceramic loaded with SnO2 / SnO catalyst.

[0015] In step (1) of the present invention, the mass ratio of the porogen zinc carbonate to calcium carbonate is 1-4:1, preferably 2-3:1;

[0016] The mass ratio of the porogen to the aluminum titanate powder is 0.01-0.05:1, such as 0.02:1, 0.03:1, 0.04:1, 0.05:1, etc., preferably 0.025-0.035:1;

[0017] The mass ratio of magnesium oxide to aluminum titanate powder is 0.02-0.05:1, preferably 0.03-0.04:1;

[0018] The calcination temperature is 900-1200° C., preferably 1000-1100° C.; the calcination time is 2-6 hours, preferably 3-5 hours;

[0019] After calcination, the aluminum titanate porous ceramic powder is crushed and passed through a 60 μm sieve to obtain the aluminum titanate porous ceramic.

[0020] In step (2) of the present invention, the mass ratio of tin nitrate to stannous nitrate is 1-7:1, for example, 2:1, 3:1, 4:1, 5:1, 6:1, etc., preferably 3-5:1;

[0021] The soaking temperature is 30-70°C, such as 40°C, 50°C, 60°C, 70°C, etc., preferably 40-60°C; the soaking time is 2-8h, preferably 3-6h;

[0022] In step (3) of the present invention, the calcination temperature is 700-1200° C., preferably 800-1000° C.; the calcination time is 3-6 hours, preferably 4-5 hours;

[0023] In the present invention, the tin content in the spherical aluminum titanate porous ceramic loaded SnO2 / SnO catalyst is 5-20wt%, preferably 10-15wt%; the particle size of the spherical aluminum titanate porous ceramic loaded SnO2 / SnO catalyst is 3-5mm.

[0024] On the other hand, the present invention also provides a method for preparing ethyl methacrylate using the above-mentioned spherical aluminum titanate porous ceramic loaded SnO2 / SnO catalyst.

[0025] In the present invention, a method for preparing ethyl methacrylate using the above-mentioned spherical aluminum titanate porous ceramic loaded SnO2 / SnO catalyst adopts a reactive distillation method. The reactive distillation system is configured with a reactor as a reaction device, a storage tank for loading the catalyst in the external circulation of the reactor, and a distillation tower for separating methanol, which catalyzes methyl methacrylate and ethanol to undergo an ester exchange reaction to produce ethyl methacrylate.

[0026] In a preferred solution, multiple sets of reaction distillation systems are connected in series, and each set of reaction distillation systems is equipped with a reactor as a reaction device, a storage tank for loading catalyst in the reactor external circulation, and a distillation tower for separating methanol.

[0027] In the present invention, a spherical aluminum titanate porous ceramic loaded SnO2 / SnO catalyst is loaded in a catalyst loading tank.

[0028] The present invention adopts a type in which the catalyst is loaded in a storage tank outside the reactor, methyl methacrylate and ethanol react in the catalyst storage tank, the reactor is used as a reboiler, and the generated by-product methanol is heated in the reactor and removed through a distillation tower, thereby avoiding damage to the catalyst by the stirrer in the reactor and ensuring the integrity of the catalyst.

[0029] The present invention adopts a series connection mode of multiple reaction distillation systems, and methyl methacrylate is added in batches to ensure that the ethanol conversion rate is greater than 99.9%.

[0030] In the present invention, a plurality of reaction distillation systems are connected in series, and more preferably two reaction distillation systems are connected in series.

[0031] In the present invention, the ratio of the amount of catalyst used in a single kettle to the ethanol feed flow rate is 10-30:1, preferably 15-25:1.

[0032] In the present invention, the reactive distillation system controls the top pressure of the distillation tower to 0.1-0.15 MPaG, preferably 0.11-0.12 MPaG, the top temperature to 60-70°C, preferably 63-67°C, the temperature in the reactor to 100-120°C, preferably 105-110°C, and the single reactor reaction time to 3-6h, preferably 4-5h by adding nitrogen.

[0033] In the present invention, the molar ratio of methyl methacrylate to ethanol is 3-8:1, preferably 4-6:1. More preferably, methyl methacrylate is evenly distributed into multiple reaction systems.

[0034] In the present invention, a polymerization inhibitor is further added to the reactive distillation system, and the polymerization inhibitor is at least one of p-methoxyphenol, hydroquinone, ZJ-701, ZJ-705, ZJ-706 and ZJ-709, preferably ZJ-701.

[0035] In the present invention, the mass ratio of the polymerization inhibitor to methyl methacrylate is 0.001-0.005:1, preferably 0.002-0.003:1.

[0036] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0037] 1) The aluminum titanate porous ceramic of the present invention is loaded with SnO2 / SnO catalyst and applied to the reaction of preparing ethyl methacrylate by ester exchange between methyl methacrylate and ethanol, and has high catalytic activity, an ethanol conversion rate of more than 99.8%, and an ethyl methacrylate selectivity of more than 99%.

[0038] 2) In the method for preparing ethyl methacrylate by ester exchange reaction between methyl methacrylate and ethanol, the catalyst is loaded in a storage tank outside the reactor, thereby avoiding damage to the catalyst by the stirrer in the reactor and prolonging the service life of the catalyst.

[0039] 3) In a preferred embodiment of the present invention, multiple sets of reaction distillation systems are connected in series, and methyl methacrylate is added in batches, thereby realizing a continuous reaction mode with low labor intensity.

[0040] 4) In the method for preparing ethyl methacrylate by transesterification of methyl methacrylate with ethanol of the present invention, there is no waste liquid containing catalyst in the whole reaction process, and the catalyst is directly separated from the reaction liquid, which is green and environmentally friendly and can be used for large-scale continuous production of ethyl methacrylate. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 The present invention is a schematic diagram of a reactive distillation device system for preparing ethyl methacrylate.

[0042] Among them, 1 is a reaction distillation system A, 11 is a catalyst storage tank A, 12 is a reactor A, 13 is a distillation tower A, 2 is a reaction distillation system B, 21 is a catalyst storage tank B, 22 is a reactor B, and 23 is a distillation tower B. DETAILED DESCRIPTION

[0043] The present invention is further described below by way of examples, which are not limited to the following examples. The present invention extends to any new features or any new combination disclosed in the specification, and any new method or process steps or any new combination disclosed.

[0044] like Figure 1 As shown, in the method for preparing ethyl methacrylate by transesterification of methyl methacrylate and ethanol of the present invention, two sets of reaction and distillation systems are used in series, namely, reaction and distillation system A1 and reaction and distillation system B2, reaction and distillation system A1 includes reaction kettle A12, external catalyst storage tank A11 and distillation tower A13, reaction and distillation system B2 includes reaction kettle B22, external catalyst storage tank B21 and distillation tower B23.

[0045] In the preparation method of the present invention, a certain amount of aluminum titanate porous ceramic loaded SnO2 / SnO catalyst is evenly filled into the external catalyst storage tank A11 in the reaction distillation system A1 and the reaction distillation system B 2, the raw material ethanol is transported to the pipeline below the catalyst storage tank A11 in the reaction distillation system A1 through a pipeline and enters the reaction system. The mixed solution of methyl methacrylate and the polymerization inhibitor is evenly distributed through pipelines and transported to the pipeline below the catalyst storage tank A11 in the A1 system and the pipeline below the catalyst storage tank B21 in the B2 system and enters the reaction system. The reaction liquid in the reactor A12 is transported to the pipeline below the catalyst storage tank B21 in the reaction system B2 through a lower liquid pipeline and enters the B2 reaction system. The reaction liquids in the reactors A12 and B22 flow back to the reactor through the lower liquid pipelines after passing through the catalyst storage tanks A11 and B21 for cyclic reaction. The reactors A12 and B22 are respectively provided with distillation towers A13 and B23 above the heads. The methanol generated in the reactors A12 and B22 enters the distillation towers A13 and B23 for removal. The reaction liquid in the reactor B22 of the B2 system is discharged through the lower liquid pipeline, which is the qualified reaction liquid after the reaction.

[0046] The present invention adopts a catalyst loaded in a catalyst storage tank of an external reactor, methyl methacrylate and ethanol react in the catalyst storage tank, the reactor is used as a reboiler, and the generated by-product methanol is heated in the reactor and removed through a distillation tower, thereby avoiding damage to the catalyst by the stirrer in the reactor and ensuring the integrity of the catalyst.

[0047] The present invention is further explained below by more specific examples, but does not constitute any limitation.

[0048] 1. Sources of main raw materials in the examples:

[0049] Zinc carbonate, analytical grade, from Qianyan Chemical Technology (Wuhan) Co., Ltd.;

[0050] Calcium carbonate, Jiangsu Bosite Chemical Technology Co., Ltd., analytical grade;

[0051] Aluminum titanate powder, Hubei Longxin Chemical Industry Co., Ltd., industrial grade;

[0052] Magnesium oxide, Jiangsu Runfeng Synthetic Technology Co., Ltd., industrial grade;

[0053] Tin nitrate, analytical grade, Beijing Inokai Technology Co., Ltd.;

[0054] Stannous nitrate, analytical grade, Beijing Inokai Technology Co., Ltd.;

[0055] Glycerol, analytical grade, Beijing Inokai Technology Co., Ltd.;

[0056] Ethanol, Shandong Jinli Chemical Co., Ltd., industrial grade;

[0057] Methyl methacrylate, Wanhua Chemical Group Co., Ltd., industrial grade;

[0058] 701 inhibitor, Suqian Liansheng Technology Co., Ltd., industrial grade;

[0059] 2. Product analysis method in the embodiment:

[0060] Physical adsorption instrument was used to determine the BET value of the catalyst. Instrument manufacturer and model: MICROMERITICS (USA) ASAP2020;

[0061] The gas chromatography analysis used the correction factor method, instrument manufacturer and model: Shimadzu 1020-plus.

[0062] Embodiment 1:

[0063] The porous ceramic-supported SnO2 / SnO catalyst is prepared by the following steps:

[0064] (1) adding 10 g of zinc carbonate, 10 g of calcium carbonate and 40 g of magnesium oxide to 2000 g of aluminum titanate powder, stirring evenly, and placing in a roasting furnace for roasting at a temperature of 900° C. for a roasting time of 2 h; crushing the roasted aluminum titanate porous ceramic and passing through a 60 μm sieve to obtain an aluminum titanate porous ceramic;

[0065] (2) 1000 g of the porous aluminum titanate ceramic obtained in step (1) is added to a 5 L reactor, and then 500 g of a 1 wt % tin nitrate solution in glycerol and 500 g of a 1 wt % stannous nitrate solution in glycerol are added, stirred evenly, heated to 30° C., and soaked for 8 h to obtain a slurry porous ceramic / tin salt composite material, which is processed into a spherical shape by a granulator, placed in a calcination furnace, and calcined at 700° C. for 6 h to obtain a spherical tin-modified molecular sieve-loaded solid acid catalyst, the tin content of which is measured to be 5.2 wt %, and the particle size is 3-5 mm.

[0066] Embodiment 2:

[0067] The porous ceramic-supported SnO2 / SnO catalyst is prepared by the following steps:

[0068] (1) adding 80 g of zinc carbonate, 20 g of calcium carbonate and 100 g of magnesium oxide to 2000 g of aluminum titanate powder, stirring evenly, and placing the mixture in a calcining furnace for calcining at a temperature of 1200° C. for 6 h; crushing the calcined aluminum titanate porous ceramic and passing it through a 60 μm sieve to obtain an aluminum titanate porous ceramic;

[0069] (2) 1000 g of the aluminum titanate porous ceramic obtained in step (1) is added to a 5 L reactor, and then 1400 g of a 1 wt % tin nitrate solution in glycerol and 200 g of a 1 wt % stannous nitrate solution in glycerol are added, stirred evenly, heated to 70° C., and soaked for 2 h to obtain a slurry porous ceramic / tin salt composite material, which is processed into a spherical shape by a granulator, placed in a calcination furnace, and calcined at 1200° C. for 3 h to obtain a spherical tin-modified molecular sieve-loaded solid acid catalyst, the tin content of which is measured to be 12.7 wt %, and the particle size is 3-5 mm.

[0070] Embodiment 3:

[0071] The porous ceramic-supported SnO2 / SnO catalyst is prepared by the following steps:

[0072] (1) adding 80 g of zinc carbonate, 20 g of calcium carbonate and 100 g of magnesium oxide to 2000 g of aluminum titanate powder, stirring evenly, and placing the mixture in a calcining furnace for calcining at a temperature of 1200° C. for 6 h; crushing the calcined aluminum titanate porous ceramic and passing it through a 60 μm sieve to obtain an aluminum titanate porous ceramic;

[0073] (2) 1000 g of the porous aluminum titanate ceramic obtained in step (1) is added to a 5 L reactor, and then 2800 g of a 1 wt % tin nitrate solution in glycerol and 400 g of a 1 wt % stannous nitrate solution in glycerol are added, stirred evenly, heated to 70° C., and soaked for 8 h to obtain a slurry porous ceramic / tin salt composite material, which is processed into a spherical shape by a granulator, placed in a calcination furnace, and calcined at 1200° C. for 6 h to obtain a spherical tin-modified molecular sieve-loaded solid acid catalyst, the tin content of which is measured to be 19.6 wt %, and the particle size is 3-5 mm.

[0074] Embodiment 4-8

[0075] refer to Figure 1 , 750 g of the porous ceramic-supported SnO2 / SnO catalyst prepared in Example 1 was evenly loaded into two reactor external storage tanks. First, 70 l of polymerization inhibitor was added to methyl methacrylate to prepare a methyl methacrylate solution. 1 / 2 of the 70 l solution of methyl methacrylate and ethanol were added to the feed position of the first reactor external storage tank in a certain proportion, and the other 1 / 2 of the 70 l solution of methyl methacrylate was added to the feed position of the second reactor external storage tank. The reaction pressure of the two systems was controlled to be 0.1 MPaG by adding nitrogen. The tower top temperature was maintained at 60 ° C by adjusting the tower oil bath temperature. The temperature of the reactor was 100 ° C. The specific reaction process conditions and reaction results of Examples 4-8 are shown in Table 1.

[0076] Table 1

[0077]

[0078]

[0079] In Examples 4-8, the porous ceramic-supported SnO2 / SnO catalyst prepared by Example 1 had an ethanol conversion greater than 99.8% and a product ethyl methacrylate selectivity greater than 99%.

[0080] Examples 9-13

[0081] 600 g of the porous ceramic-supported SnO2 / SnO catalyst prepared in Example 2 was loaded into an external storage tank of the reactor. First, 701 of polymerization inhibitor was added to methyl methacrylate to prepare a methyl methacrylate solution. 1 / 2 of the 701 solution of methyl methacrylate and ethanol were added to the feed position of the first set of external storage tanks of the reactor in a certain proportion, and the other 1 / 2 of the 701 solution of methyl methacrylate was added to the feed position of the second set of external storage tanks of the reactor. The reaction pressure of the two systems was controlled to be 0.15 MPaG by adding nitrogen. The top temperature of the tower was maintained at 70°C by adjusting the oil bath temperature of the tower bottom. The temperature of the reactor was 120°C. The specific reaction process conditions and reaction results of Examples 9-13 are shown in Table 2.

[0082] Table 2

[0083]

[0084]

[0085] In Examples 9-13, the porous ceramic-supported SnO2 / SnO catalyst prepared by Example 2 had an ethanol conversion greater than 99.8% and a product ethyl methacrylate selectivity greater than 99%.

[0086] Examples 14-18

[0087] 900 g of the porous ceramic-supported SnO2 / SnO catalyst prepared in Example 3 was loaded into an external storage tank of the reactor. First, 701 of polymerization inhibitor was added to methyl methacrylate to prepare a methyl methacrylate solution. 1 / 2 of the 701 solution of methyl methacrylate and ethanol were added to the feed position of the first set of external storage tanks of the reactor in a certain proportion, and the other 1 / 2 of the 701 solution of methyl methacrylate was added to the feed position of the second set of external storage tanks of the reactor. The reaction pressure of the two systems was controlled to be 0.11 MPaG by adding nitrogen. The top temperature of the tower was maintained at 63°C by adjusting the oil bath temperature of the tower bottom. The temperature of the reactor was 110°C. The specific reaction process conditions and reaction results of Examples 14-18 are shown in Table 3.

[0088] Table 3

[0089]

[0090]

[0091] In Examples 14-18, the porous ceramic-supported SnO2 / SnO catalyst prepared by Example 3 had an ethanol conversion greater than 99.8% and a product ethyl methacrylate selectivity greater than 99%.

[0092] Comparative Example 1

[0093] The difference from Example 4 is that the porous ceramic-supported SnO2 / SnO catalyst prepared in Example 1 is replaced by purchased tetrabutyl titanate liquid. First, 701 polymerization inhibitor is added to methyl methacrylate to prepare a methyl methacrylate solution, and then tetrabutyl titanate liquid is added to the solution to prepare tetrabutyl titanate and 701 solution of methyl methacrylate. The mass ratio of tetrabutyl titanate to methyl methacrylate is 0.01:1. 1 / 2 of the tetrabutyl titanate and 701 solution of methyl methacrylate and ethanol are added to the feed position of the external storage tank of the first set of reactors in the same proportion, and the other 1 / 2 of the tetrabutyl titanate and 701 solution of methyl methacrylate are added to the feed position of the external storage tank of the second set of reactors. The reaction pressure of the two systems is controlled to be 0.1 MPaG by adding nitrogen, and the top temperature of the tower is maintained at 60°C by adjusting the oil bath temperature of the tower bottom. The temperature of the reactor is 100°C, the conversion rate of ethanol is 88.7%, and the selectivity of ethyl methacrylate is 98.4%. The reaction activity is relatively low during the reaction process, and the separation process needs to consider the removal of tetrabutyl titanate in the reaction solution.

Claims

1. A porous ceramic-supported SnO2 / SnO catalyst, characterized in that: The catalyst uses aluminum titanate porous ceramics prepared by using zinc carbonate and calcium carbonate as porogens as a carrier, and the loaded active component is a SnO2 / SnO mixture. The tin content in the catalyst is 5-20wt%, preferably 10-15wt%.

2. The method for preparing the porous ceramic-supported SnO2 / SnO catalyst according to claim 1, characterized in that: The following steps are involved: (1) Using aluminum titanate powder as a raw material, a mixture of zinc carbonate and calcium carbonate as a porogen, and magnesium oxide as a stabilizer, and calcining at elevated temperatures to obtain aluminum titanate porous ceramics; (2) soaking the aluminum titanate porous ceramic obtained in step (1) in a saturated glycerol solution of tin nitrate and stannous nitrate so that the tin nitrate and stannous nitrate adhere to the inside of the porous ceramic particles to obtain a porous ceramic / tin salt composite material; (3) The porous ceramic / tin salt composite material obtained in step (2) is calcined and granulated to obtain a spherical aluminum titanate porous ceramic loaded with SnO2 / SnO catalyst.

3. The preparation method according to claim 2, characterized in that: In step (1), the mass ratio of the porogen zinc carbonate to calcium carbonate is 1-4:1, preferably 2-3:1; and / or The mass ratio of the porogen to the aluminum titanate powder is 0.01-0.05:1, preferably 0.025-0.035:1; and / or The mass ratio of magnesium oxide to aluminum titanate powder is 0.02-0.05:1, preferably 0.03-0.04:1; Preferably, the calcination temperature is 900-1200°C, preferably 1000-1100°C; the calcination time is 2-6h, preferably 3-5h; and / or After calcination, the aluminum titanate porous ceramic powder is crushed and passed through a 60 μm sieve to obtain the aluminum titanate porous ceramic.

4. The preparation method according to claim 2, characterized in that: In step (2), the mass ratio of tin nitrate to stannous nitrate is 1-7:1, preferably 3-5:1; Preferably, the soaking temperature is 30-70°C, preferably 40-60°C; the soaking time is 2-8h, preferably 3-6h.

5. The preparation method according to claim 2, characterized in that: In step (3), the calcination temperature is 700-1200° C., preferably 800-1000° C.; the calcination time is 3-6 hours, preferably 4-5 hours; Preferably, the tin content in the spherical aluminum titanate porous ceramic supported SnO2 / SnO catalyst is 5-20wt%, preferably 10-15wt%; More preferably, the particle size of the spherical aluminum titanate porous ceramic loaded SnO2 / SnO catalyst is 3-5 mm.

6. Use of the porous ceramic-supported SnO2 / SnO catalyst according to claim 1 or the porous ceramic-supported SnO2 / SnO catalyst prepared by the preparation method according to any one of claims 2 to 5 in catalyzing the transesterification reaction of methyl methacrylate and ethanol to prepare ethyl methacrylate.

7. A method for preparing ethyl methacrylate, characterized in that: The following steps are involved: A reactive distillation method is adopted, and the reactive distillation system is configured with a reactor as a reaction device, a storage tank for loading a catalyst in an external circulation of the reactor, and a distillation tower for separating methanol, catalyzing methyl methacrylate and ethanol to undergo an ester exchange reaction to produce ethyl methacrylate, wherein the catalyst is the porous ceramic-loaded SnO2 / SnO catalyst according to claim 1 or the porous ceramic-loaded SnO2 / SnO catalyst prepared by the preparation method according to any one of claims 2-5.

8. The method for preparing ethyl methacrylate according to claim 7, characterized in that: Methyl methacrylate and ethanol react in a catalyst storage tank, and the reactor is used as a reboiler. The by-product methanol generated is heated in the reactor and removed through a distillation tower; Preferably, the reaction is carried out in a manner of connecting multiple sets of reaction distillation systems in series, and the methyl methacrylate is added in batches to the multiple sets of reaction distillation systems in series; preferably, the methyl methacrylate is evenly added to the multiple sets of reaction distillation systems in series; More preferably, the reaction is carried out by connecting two sets of reaction distillation systems in series.

9. The method for preparing ethyl methacrylate according to claim 7 or 8, characterized in that: The ratio of the amount of catalyst used in a single kettle to the ethanol feed flow rate is 10-30:1, preferably 15-25:1; and / or The molar ratio of methyl methacrylate to ethanol is 3-8:1, preferably 4-6:1; Preferably, the reactive distillation system controls the top pressure of the distillation tower to 0.1-0.15 MPaG, preferably 0.11-0.12 MPaG, the top temperature to 60-70°C, preferably 63-67°C, the temperature in the reactor to 100-120°C, preferably 105-110°C, and the single-reactor reaction time to 3-6h, preferably 4-5h by adding nitrogen.

10. The method for preparing ethyl methacrylate according to claim 9, characterized in that: A polymerization inhibitor is also added to the reactive distillation system, wherein the polymerization inhibitor is at least one of p-methoxyphenol, hydroquinone, ZJ-701, ZJ-705, ZJ-706 and ZJ-709, preferably ZJ-701; Preferably, the mass ratio of the polymerization inhibitor to methyl methacrylate is 0.001-0.005:1, preferably 0.002-0.003:1.

Citation Information

Patent Citations

  • Preparation method of ethyl methacrylate

    CN102766049A